Reduced ENA78 levels as novel biomarker for major depressive disorder and venlafaxine efficiency: Result from a prospective longitudinal study. (July 2017) - Li, Zezhi; Wang, Zuowei; Zhang, Chen; Chen, Jun; Su, Yousong; Huang, Jia; Yi, Zhenghui; Yuan, Chengmei; Hong, Wu; Wang, Yong; Wu, Zhiguo; Hu, Yingyan; et al.
Highlights: Although lines of evidence demonstrated that cytokines play an important role in the pathogenesis of major depressive disorder (MDD), none of the them have been established as reliable biomarkers. We use our previous whole-genome cRNA microarray data to identify epithelial cell-derived neutrophil-activating peptide 78 (ENA78), the most differentially expressed cytokine in peripheral blood between MDD patients and healthy controls; and then we confirmed the result by the quantitative reverse transcription-polymerase chain reaction (RT-qPCR) and enzyme-linked immunosorbent assay (ELISA) for mRNA and protein level, respectively, in an independent drug-naïve first-episode sample set. In addition, to replicate the role of plasma ENA 78 in MDD, and determine the role of ENA78 on the venlafaxine efficiency, we further detected the plasma ENA78 in another independent 8- week follow-up sample set. We found that both of mRNA and plasma of ENA78 decreased in MDD patients, and displayed much lower after venlafaxine treatment. We also found that venlafaxine non-responders had lower level of peripheral plasma ENA78 prior to treatment than responders. Our findings for the first time provided strong evidence that the ENA78 may play a key role of mediator in pathogenesis of MDD and in the mechanism of vinlafaxine effects on MDD indicating that reduced ENA78 may be a potential biomarker for diagnosing of MDD and predicting of response to venlafaxine. Abstract: Although lines of evidence demonstrated that cytokines play an important role in the pathogenesis of major depressive disorder (MDD), none of the them have been established as reliable biomarkers. We use our previous whole-genome cRNA microarray data to identify epithelial cell-derived neutrophil-activating peptide 78 (ENA78), the most differentially expressed cytokine in peripheral blood between MDD patients and healthy controls; and then we confirmed the result by the quantitative reverse transcription-polymerase chain reaction (RT-qPCR) and enzyme-linked immunosorbent assay (ELISA) for mRNA and protein level, respectively, in an independent drug-naïve first-episode sample set. In addition, to replicate the role of plasma ENA 78 in MDD, and determine the role of ENA78 on the venlafaxine efficiency, we further detected the plasma ENA78 in another independent 8- week follow-up sample set. We found that both of mRNA and plasma of ENA78 decreased in MDD patients, and displayed much lower after venlafaxine treatment. We also found that venlafaxine non-responders had lower level of peripheral plasma ENA78 prior to treatment than responders. Our findings for the first time provided strong evidence that the ENA78 may play a key role of mediator in pathogenesis of MDD and in the mechanism of vinlafaxine effects on MDD indicating that reduced ENA78 may be a potential biomarker for diagnosing of MDD and predicting of response to venlafaxine.